2019
DOI: 10.5539/ies.v12n9p54
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality and MS-Kinect in the Learning of Basic Mathematics: KARMLS Case

Abstract: By its nature, the learning of certain complex contents has always been a focus of attention and a challenge in the study of mathematics. This fact acquires greater importance if it is about the learning of children, because the psycho-cognitive skills of this type of user, especially when they attend the first levels of Basic General Education are not yet mature. As a result, children are unable to assimilate correctly and easily certain content of an abstract nature during the early stages of mathematics lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…8 The results of research by Raul Lozada Yones, et al show that a computer system called "Kinect-Based Augmented Reality Mathematics Learning System -KARMLS", whose design and development uses Augmented Reality technology and motion sensors implemented on the MS-Kinect camera which is applied, has a positive effect on learning when used as a medium and it is more effective on its performance, and is more motivated and gives a positive response to the use of AR. 9 In line with Ilyas Akkus' research, it shows that AR applications developed for geometry learning using gadgets can develop spatial intelligence and contribute positively to students' academic success. 10 Another study was also conducted by Guntur and Setyaningrum whose research results showed that AR is very suitable to be developed on geometric materials but does not rule out the possibility to be developed on different materials such as vectors, algebra, and others.…”
Section: Introductionmentioning
confidence: 53%
“…8 The results of research by Raul Lozada Yones, et al show that a computer system called "Kinect-Based Augmented Reality Mathematics Learning System -KARMLS", whose design and development uses Augmented Reality technology and motion sensors implemented on the MS-Kinect camera which is applied, has a positive effect on learning when used as a medium and it is more effective on its performance, and is more motivated and gives a positive response to the use of AR. 9 In line with Ilyas Akkus' research, it shows that AR applications developed for geometry learning using gadgets can develop spatial intelligence and contribute positively to students' academic success. 10 Another study was also conducted by Guntur and Setyaningrum whose research results showed that AR is very suitable to be developed on geometric materials but does not rule out the possibility to be developed on different materials such as vectors, algebra, and others.…”
Section: Introductionmentioning
confidence: 53%
“…The human action sequence is continuous and changes with time. The change of joint angle before and after forms the value of angular velocity ω. the limb vector and the angular velocity of active joint angle are the characteristics of active action, representing the overall movement of human limbs and trunk [22]. The bending of human limbs and trunk is reflected by the change of the distance between joint points.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the didactic proposals outlined, it can be said that the use of AR technology is an educational innovation, which can make a positive contribution to improving the understanding of geometry concepts, developing spatial visualization (Ahmad, 2021;Amir et al, 2020b;Elsayed & Al-Najrani, 2021;Flores-Bascuñana et al, 2020;Ozcakir & Cakiroglu, 2021;Schutera et al, 2021;Vakaliuk et al, 2020;Velázquez & Méndez, 2021a), and increased student motivation (Fatimah et al, 2019;Lozada-Yánez et al, 2019;Mailizar & Johar, 2021;Sudirman et al, 2020). Student motivation and their involvement in learning is key to achieving effective learning (Fernández-Enríquez & Delgado-Martín, 2020).…”
Section: Figure 7: Distribution Of Ar To Solve the Problems In Mathem...mentioning
confidence: 99%